2014
DOI: 10.1038/ncomms4670
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing adult nerve regeneration through the knockdown of retinoblastoma protein

Abstract: Tumour suppressor pathways may offer novel targets capable of altering the plasticity of post-mitotic adult neurons. Here we describe a role for retinoblastoma (Rb) protein, widely expressed in adult sensory neurons and their axons, during regeneration. In adult sensory neurons, Rb siRNA knockdown or Rb1 deletion in vitro enhances neurite outgrowth and branching. Plasticity is achieved in part through upregulation of neuronal PPARγ; its antagonism inhibits Rb siRNA plasticity whereas a PPARγ agonist increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…Moreover, KO mouse models have revealed the role of RB during neuronal differentiation and migration, as well as in the regulation of cell death in the embryo and adult brain (Andrusiak et al, 2011;Ghanem et al, 2012;McClellan et al, 2007;Christie et al, 2014;Ferguson et al, 2005;Macleod et al, 1996;Vandenbosch et al, 2016;Yu et al, 2012). The finding that lack of the RB1 gene is associated with structural brain abnormalities in human (Mitter et al, 2011;Rodjan et al, 2010), and inactivation of RB family proteins affects cell cycle and cell death in human ESCs (Conklin et al, 2012), suggest that RB might have a role during human brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KO mouse models have revealed the role of RB during neuronal differentiation and migration, as well as in the regulation of cell death in the embryo and adult brain (Andrusiak et al, 2011;Ghanem et al, 2012;McClellan et al, 2007;Christie et al, 2014;Ferguson et al, 2005;Macleod et al, 1996;Vandenbosch et al, 2016;Yu et al, 2012). The finding that lack of the RB1 gene is associated with structural brain abnormalities in human (Mitter et al, 2011;Rodjan et al, 2010), and inactivation of RB family proteins affects cell cycle and cell death in human ESCs (Conklin et al, 2012), suggest that RB might have a role during human brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, RB was described as regulating the G1/S transition of the cell cycle through E2F-mediated transcriptional regulation in many tissues, including the nervous system (Classon and Harlow, 2002;McClellan and Slack, 2006;Julian et al, 2016;MacPherson et al, 2003;Naser et al, 2016). Recently, studies of brain-specific Rb1-KO mice revealed other roles of the Rb1 gene that extend beyond cell cycle control, such as regulation of neuronal differentiation and migration (Andrusiak et al, 2011;Ghanem et al, 2012;McClellan et al, 2007;Christie et al, 2014;Ferguson et al, 2005). Moreover, the lack of RB promotes apoptosis in some cell types, but not in others, through p53-dependent or -independent pathways (Macleod et al, 1996;Vandenbosch et al, 2016;Yu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, expression of another transcription factor PPARγ was altered downstream of Rb1 inhibition. Further studies on the impact of PPARγ activation on neurite outgrowth suggest that PPARγ could be a potential mediator for Rb1 suppression-mediated growth effects in neurons [4]. However, the limited roles of the transcription factors in the axoplasm while there is persistent expression of Rb1 in local axons raises the possibility that additional mechanisms may also be involved.…”
mentioning
confidence: 99%
“…Relieving the growth inhibition posed by such inhibitors, for example, targeting the central growth 'brake' PTEN, has proven remarkably effective in increasing the extent by which peripheral axons regenerate [3]. Having experience with this approach in our laboratory, we have recently identified another tumor suppressor, retinoblastoma protein (Rb1), as a novel target for improving PNS regeneration [4]. Rb1, since its identification as the first tumor suppressor, has attracted cancer biologists for its robust growth inhibitory properties in epithelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation